Tumour microbiomes and Fusobacterium genomics in Vietnamese colorectal cancer patients - Tran, Hoang N. H.; Thu, Trang Nguyen Hoang; Nguyen, Phu Huu; Vo, Chi Nguyen; Doan, Khanh Van; Nguyen Ngoc Minh, Chau; Nguyen, Ngoc Tuan; Ta, Van Ngoc Duc; Vu, Khuong An; Hua, Thanh Danh; Nguyen, To Nguyen Thi; Van, Tan Trinh; et al. (NPJ biofilms and microbiomes, 2022)
Perturbations in the gut microbiome have been associated with colorectal cancer (CRC), with the colonic overabundance of Fusobacterium nucleatum shown as the most consistent marker. Despite its significance in the promotion of CRC, genomic studies of Fusobacterium is limited. We enrolled 43 Vietnamese CRC patients and 25 participants with non-cancerous colorectal polyps to study the colonic microbiomes and genomic diversity of Fusobacterium in this population, using a combination of 16S rRNA gene profiling, anaerobic microbiology, and whole genome analysis. Oral bacteria, including F. nucleatum and Leptotrichia , were significantly more abundant in the tumour microbiomes. We obtained 53 Fusobacterium genomes, representing 26 strains, from the saliva, tumour and non-tumour tissues of six CRC patients. Isolates from the gut belonged to diverse F. nucleatum subspecies ( nucleatum , animalis , vincentii , polymorphum ) and a potential new subspecies of Fusobacterium periodonticum . The Fusobacterium population within each individual was distinct and in some cases diverse, with minimal intra-clonal variation. Phylogenetic analyses showed that within four individuals, tumour-associated Fusobacterium were clonal to those isolated from non-tumour tissues. Genes encoding major virulence factors (Fap2 and RadD) showed evidence of horizontal gene transfer. Our work provides a framework to understand the genomic diversity of Fusobacterium within the CRC patients, which can be exploited for the development of CRC diagnostic and therapeutic options targeting this oncobacterium.